Evaluation of Histone 3 Lysine 27 Trimethylation (H3K27me3) and Enhancer of Zest 2 (EZH2) in Pediatric Glial and Glioneuronal Tumors Shows Decreased H3K27me3 in H3F3A K27M Mutant Glioblastomas. (6th March 2013) - Venneti, Sriram; Garimella, Mihir T.; Sullivan, Lisa M.; Martinez, Daniel; Huse, Jason T.; Heguy, Adriana; Santi, Mariarita; Thompson, Craig B.; Judkins, Alexander R.
Abstract H3F3A mutations are seen in ∼30% of pediatric glioblastoma (GBMs) and involve either the lysine residue at position 27 (K27M) or glycine at position 34 (G34R/V). Sixteen genes encode histone H3, each variant differing in only a few amino acids. Therefore, how mutations in a single H3 gene contribute to carcinogenesis is unknown. H3F3A K27M mutations are predicted to alter methylation of H3K27. H3K27me3 is a repressive mark critical to stem cell maintenance and is mediated by EZH2, a member of the polycomb‐group (PcG) family. We evaluated H3K27me3 and EZH2 expression using immunohistochemistry in 76 pediatric brain tumors. H3K27me3 was lowered/absent in tumor cells but preserved in endothelial cells and infiltrating lymphocytes in six out of 20 GBMs. H3K27me3 showed strong immunoreactivity in all other tumor subtypes. Sequencing of GBMs showed H3F3A K27M mutations in all six cases with lowered/absent H3K27me3. EZH2 expression was high in GBMs, but absent/focal in other tumors. However, no significant differences in EZH2 expression were observed between H3F3A K27M mutant and wild type GBMs, suggesting that EZH2 mediated trimethylation of H3K27 is inhibited in GBM harboring K27M mutations. Our results indicate that H3F3A K27M mutant GBMs show decreased H3K27me3 that may be of both diagnostic and biological relevance.